Molecular Genetics Study on Autistic Patients in Iraq - K. Karmeet, Basheer; A. Al-Kazaz, Abdul Kareem; Saber, Mahdi (Iraqi Journal of Science, 2023)
This study reflected on the relationship between contactin associated protein-like2 gene (CNTNAP2) and autism spectrum disorders. The study includes forty autisticpatients and forty non autistic children as control groups (twenty unaffected siblingand twenty unrelated children). DNA was extracted from Blood samples formolecular detection of CNTNAP2 mutations associated with ASDs by usingPolymerase Chain Reaction (PCR) technique and sequencing analysis. PCR reactionwas performed to amplify exon 20 of CNTNAP2 gene. The PCR results revealed thatidentical bands related to exon 20 of CNTNAP2 gene were present in all samples.Therefore, five samples (four from autistic patients and one from control sibling)were selected for genotype analysis of CNTNAP2 (exon 20) by direct sequencing.Genotype analysis revealed that there were no any variants in CNTNAP2 (exon 20),but it shows that two different mutations were identified in non coding region(introns) of the CNTNAP2 gene (Single Nucleotide Polymorphisms (SNPs),ID SNP:rs3779032 A/G in 2118282 position and ID SNP: rs3779031 A/C in 2118436position). rs3779031 A/C are located at intron 19 while SNP rs3779032 A/G arelocated at intron 21. These mutations were seen only in autistic patients but notpresent in control sample. The current study showed that two common SNPs(rs3779031 and rs3779032) in CNTNAP2 were strongly associated with ASDs,where the frequencies of these SNPs were relatively high. SNP rs3779032 wereidentified in two autistic patients while rs3779031 were identified in three autisticpatients from four unrelated families with ASDs.